APLIKASI COMMODITY SYSTEM ASSESMENT METHOD (CSAM) DALAM JALUR DISTRIBUSI BUNGA GEMITIR DARI DESA BELOK SIDAN SAMPAI PENGECER DI DENPASAR - Iswara, Krisna; Admadi, Bambang; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 3 (2018): September, 2018)
The aim of this research is to know the number of distribution channel of the flower from farmers in Petang District to the retailer, to know the impact of postharvest loss on the flower of farmers from Petang District to retailers.The research used commodity system assessment method method in the form of questionnaires distributed to farmers, collectors, and flower retailers. Impact of handling during farmer level is at clearance and sorting significance reach 15,33%.At the level of collectors is on cleaning and sorting significantly reaches 5.17%. Meanwhile, at the retailer level the impact of sorting on the loss of flower interest is significant ie 12.5%. Physical damage that occurred in the form of flower broken flower at sortation. Physical damage occurs due to collisions, friction, and piles during the distribution process at the retailer level. Keywords :  CSAM , distribution channels, flower.